Witches broom disease of lime and its management - MEHDI AZADVAR, MOUSA NAJAFINIYA* and (Indian Phytopathology, 2016)
One of the major diseases of the citrus in south of Iran is Witches broom disease of Lime (WBDL). The causal agent of WBDL is Candidatus phytoplasma aurantifolia. The symptoms of disease started from one side of tree and including witches broom of twigs, shortened inter nodes, pale green in appearance, leaf little, no flowering and fruiting and finally destroying of infected plants was observed. Application of integrated management methods and cultural practices showed to be very useful in reduction of the infection rate of diseases. Control measures including: eliminating of infected tree with clear symptom, elimination of newly emerged symptomatic branches on tree, chemical or mechanical control of weeds, and periodic spray of systemic pesticides for vector control, and combination of mentioned treatments showed to be very effective for reducing the distribution rate of witches broom disease of lime. Chemical control of insect vectors is very important to reduce the rate of disease spreading.